Syahadah Rukyatulhilal Using Astro Digital Imaging: From Subjectivity to Objectivity - Ahmad Junaidi (Fakultas Syariah, 2022)
Abstract:The process of determining the beginning of the lunar month based on syahadah rukyatulhilal often contains an element of subjectivity to witnesses which can only be confirmed by oath before a judge. Technological developments are expected to increase the objectivity of the process of syahadah rukyatulhilal by attaching the hilal image generated from Astro digital imaging. This study explains the importance of a new rukyatulhilal model based on digital data as witness reinforcement in the process of syahadah rukyatulhilal. By using a scientific and a fiqhiyah approach, research shows that developing a digital data-based rukyatulhilal model is significant in avoiding the subjectivity of the process and its results. This is following the spirit exemplified by the Prophet and the fuqaha' in accepting rukyatulhilal testimony by avoiding things that raise doubts. Using image evidence from astro digital imaging to corroborate rukyatulhilal's testimony does not violate fiqh, even the status of image as evidence is the same as witness status.Keywords: astro digital imaging; image processing; syahadah rukyatulhilal.Abstrak:Proses penentuan awal bulan qamariah yang didasarkan syahadah rukyatulhilal sering kali mengandung unsur subjektifitas pada saksi yang hanya bisa dikonfirmasi dengan sumpah di depan hakim. Perkembangan teknologi diharapkan bisa meningkatkan objektifitas proses syahadah rukyatulhilal dengan lampiran citra hilal yang dihasilkan dari astro digital imaging (pencitraan digital pada objek astronomi). Penelitian ini memaparkan pentingnya model baru rukyatulhilal yang berbasis data digitalsebagai penguat saksi dalam proses syahadah rukyatulhilal. Dengan menggunakan pendekatan sains dan pendekatan fiqhiyah, penelitian menunjukkan bahwa pengembangan model rukyatulhilal yang berbasis data digital sangat penting dilakukan dalam rangka menepis subjektifitas proses dan hasilnya. Hal ini sesuai dengan semangat yang dicontohkan oleh Nabi dan fuqaha’ dalam menerima kesaksian rukyatulhilal dengan menghindari hal-hal yang menimbulkan keraguan. Penggunaan bukti citra dari astro digital imaginguntuk menguatkan kesaksian rukyatulhilal tidak menyalahi fikih, bahkan status bukti citra itu sama dengan status saksi.Kata Kunci: astro digital imaging; image processing; syahadah rukyatulhilal